PERILAKU SCHOOL BULLYING DI SDN 13 PELANGAI KACIAK KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - Riska Mayeni; Yanti Nazmai Ekaputri; Efendi Efendi; Maijem Simponi; Sefrinal Sefrinal (JURNAL MANAJEMEN PENDIDIKAN, 2022)
This study aims to identify school bullying behavior in 13 PelangaiKaciak State Elementary Schools, Pesisir Districts, Pessel Districts. The initial research subjects were all teachers and students at SD 13 Pelangaikaciak.. The research location is in the Elementary School 13 PelangaiKaciak, using a qualitative approach. The data collection method used non-participatory observation, in-depth interviews, documentation and field notes. The data analysis technique used is data collection, data reduction, data presentation and conclusion drawing. Based on the results of the study, it can be concluded that school bullying occurred at the State Elementary School 13 PelangaiKaciak with the following results. (1) teachers' lack of knowledge about school bullying, as well as the opinion of teachers who say that delinquency in their schools is still normal; (2) the reaction shown by the victim is silence, fear or crying; the perpetrator shows indifferent and happy behavior; while the audience shows a reaction, fights the perpetrator, defends the perpetrator or is silent; (3) the forms of school bullying that occur are physical (hitting with a broom handle, hitting with hands, pushing) and non-physical (verbal: threatening, forcing, shouting, teasing; direct non-verbal: yelling, scolding, ordering, pointing). with the fingers; non-verbal indirect: exclusion).